Quality of radiation protection aprons and quality control routines at different diagnostic imaging modalities - Bjørkås , Linda Wie; Blø, Sandra; Rekdal, Magnus Kristoffersen; Rusandu, Albertina (Radiography Open, 2020)
Keywords: Radiation protection apron, Quality control, Routines, Radiation protection, Radiation doses Abstract Introduction: The purpose of this project was to assess the quality of lead aprons at different departments at two hospitals and to investigate whether there was a connection between routines for controlling lead aprons and the actual condition of the lead aprons. Methods: Lead aprons were tested in several diagnostic modalities in two hospitals. The lead aprons were inspected visually and by palpation. Furthermore, the lead aprons were scanned with a fluoroscopy unit and the size of the defect was recorded. The radiation dose was measured behind defects exceeding 0,4 cm in length. Radiation protection officers at the two hospitals were contacted for a review of the procedures. Results: Defects were detected in 19% of the tested aprons. Most findings were discovered in emergency room 1, where 62,5% of the lead aprons had one or more defects. The measured radiation doses behind the defects ranged from 3.996 nGy to 83.370 nGy. No defects were detected on nuclear medicine 1, emergency room 2, CT 2 and intervention 2. Both hospitals' routines were based on the Norwegian Radiation Protection Regulations. Hospital 2 controlled most of the lead aprons one month prior to this project. Conclusion: A possible connection between the hospitals’ routines and the quality of the lead aprons is indicated by the fact that the hospital with the most defective lead aprons also had the least follow-up of the routines.